Um estudo sobre o uso da Inteligência Artificial nas empresas - Pereira, Keith Anny Borges (Brasil, 2021)
The concept of Artificial Intelligence grew with the advancement of technology and its attributions are essential in several sectors. In this sense, the objective of this work was to identify the artificial intelligence technologies used to improve or help in the growth and development of companies. The research methodology adopted for this work is based on a systematic review in order to select available research on the use of Artificial Intelligence in Companies, highlighting the most applied technologies. As a result, technologies such as big data, cloud computing and IoT (internet of things) were identified in the literature. These can be used by companies to assist with certain tasks and functions in these organizations.